Enhanced Electrical Properties of Styrene-grafted Polypropylene Insulation for Bulk Power Transmission HVDC Cables - Hao Yuan; Shixun Hu; Yao Zhou; Chao Yuan; Wenbo Song; Qing Shao; Hongwei Shi; Juan Li; Jun Hu; Qi Li; Jinliang He (CSEE Journal of Power and Energy Systems, 2024)
Polypropylene (PP) is considered to be a rather promising material for HVDC cable insulation. Grafting modi-fication has proved to be an effective method on the electrical property improvements of PP. This paper reports on the highly-enhanced electrical properties of styrene-grafted polypropylene (PP-g-St) and their related mechanism. The influence of grafting styrene on crystallization structures, thermal properties and electrical properties of PP-g-St are characterized and analyzed. These results show that PP-g-St exhibits remarkably enhanced DC volume resistivity, suppressed space charge accumulation and improved DC breakdown strengths as compared to PP. Crystallization observation shows PP-g-St has small, imperfect spherulites with indistinct boundaries, which is strongly correlated to enhanced electrical properties. This study provides an effective grafting strategy to design high-performance HVDC cable insulation materials for bulk power transmission systems.